2017
DOI: 10.1038/s41598-017-16926-w
|View full text |Cite|
|
Sign up to set email alerts
|

“Carboranyl-cysteine”—Synthesis, Structure and Self-Assembly Behavior of a Novel α-Amino Acid

Abstract: Substitution of the thiol proton in cysteine with m-carborane furnished 2-amino-3-(1,7-dicarba-closo-dodecacarboranyl-1-thio)propanoic acid (3), a boron cluster amino acid that exhibits self-assembly to form micron-sized constructs. Field emission scanning electron microscopy revealed that ethanol solutions of 3 form floret-shaped constructs, while fibrillar architectures are formed in water. Furthermore, slow evaporation of methanol solutions of 3 produced crystals whose structure was revealed by X-ray crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…[22] This modified amino acid formed floret like discs in ethanol and fibers in aqueous solutions. Crystal structures revealed the formation of bilayers via H-bonding interactions.…”
Section: Amino Acid Based Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] This modified amino acid formed floret like discs in ethanol and fibers in aqueous solutions. Crystal structures revealed the formation of bilayers via H-bonding interactions.…”
Section: Amino Acid Based Nanostructuresmentioning
confidence: 99%
“…Taking a de novo approach, Musah and co-workers synthesized a boron cluster amino acid, 2-amino-3-(1,7-dicarbaclosododecacarboranyl-1-thio)-propanoic acid, by substituting the thiol proton in cysteine with m -carborane. [22] This modified amino acid formed floret like discs in ethanol and fibers in aqueous solutions. Crystal structures revealed the formation of bilayers via H-bonding interactions.…”
Section: Amino Acid Based Nanostructuresmentioning
confidence: 99%
“…+20 ppm), analogous to that for complex 3 in DMSO-d 6 , is evident, but no rational behind this was proposed. It was simply concluded by the authors that there is no difference in the NMR spectra between aggregating and "non-aggregating" conditions, although it is not clear why an ethanolic solution should represent "non-aggregating" conditions, since closo-carborane derivatives are also known to form nano-structures in ethanol [27].…”
Section: Synthesis and Characterization Of Complexes 2-4 Andmentioning
confidence: 99%
“…As already mentioned before, aqueous self-assembly of neutral (metalla)carboranes has been so far poorly investigated, and is limited to a few examples of C-substituted closo-carboranes [26,27]. No studies on the effect of spontaneous aggregation on the biological activity profile or stability in the biological medium are found in the literature.…”
Section: Uv-vis Spectroscopy Mass Spectrometry and Nanoparticle Tracmentioning
confidence: 99%
“…[9,[35][36][37][38][39] In contrast, only a few reports exist which suggest that also non-ionic icosahedral (metalla)carboranes show a tendency to aggregate into nano-and micro-entities in aqueous solutions. [40][41][42][43][44][45][46] However, investigations which translate the physicochemical self-assembling behaviour to the biological concept of colloidal drug aggregates are missing, except our most recent work. [47] Thus, we have shown that neutral boron cluster compounds spontaneously aggregate in buffered solutions and/or in cell culture media.…”
Section: Introductionmentioning
confidence: 99%